1999
DOI: 10.1007/s002030050786
|View full text |Cite
|
Sign up to set email alerts
|

Osmoadaptation in halophilic and alkaliphilic methanotrophs

Abstract: By using (1)H- and (13)C-NMR spectroscopy, an accumulation of sucrose and two cyclic amino acids [ectoine (1,4,5, 6-tetrahydro-2-methyl-4-pyrimidine carboxylic acid) and 5-oxoproline (pyrrolidone carboxylic acid)] was detected in the halotolerant methanotrophs Methylobacter alcaliphilus 20Z and Methylobacter modestohalophilus 10S. The organic solute pool was found to increase upon raising the NaCl concentration. In M. alcaliphilus 20Z, the intracellular level of the total solutes was shown to be sufficient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 28 publications
2
92
0
Order By: Relevance
“…These results suggested a specific interaction between EctR1 and the promoter regions of the ectABC-ask and ectR1 genes. (20,40,60,80, and 160 pmol) were added to the probe. For the competition assay, an unlabeled specific DNA was added to the reaction mixture after incubation with the labeled fragment.…”
Section: Vol 192 2010 Ectoine Biosynthesis Regulation In M Alcalipmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested a specific interaction between EctR1 and the promoter regions of the ectABC-ask and ectR1 genes. (20,40,60,80, and 160 pmol) were added to the probe. For the competition assay, an unlabeled specific DNA was added to the reaction mixture after incubation with the labeled fragment.…”
Section: Vol 192 2010 Ectoine Biosynthesis Regulation In M Alcalipmentioning
confidence: 99%
“…The halotolerant obligate methanotroph Methylomicrobium alcaliphilum 20Z is capable of growth at a salinity as high as 2 M NaCl (19). It was demonstrated that in response to the elevated salinity of the growth medium, M. alcaliphilum cells accumulate ectoine as a major osmoprotective compound (20). The ectoine biosynthesis pathway in M. alcaliphilum 20Z is similar to the pathway employed by halophilic/halotolerant heterotrophs and involves three specific enzymes: diaminobutyric acid (DABA) aminotransferase (EctB), DABA acetyltransferase (EctA), and ectoine synthase (EctC) (7,21,24,30,32,49).…”
mentioning
confidence: 99%
“…Preparation of thin sections and electron microscopy were done as described previously (Khmelenina et al, 1997(Khmelenina et al, , 1999. For freeze-fractured preparations, exponentially growing cells were collected and frozen in liquid propane cooled to k196 mC with liquid nitrogen.…”
Section: Verification Of Purity Of Strain B2mentioning
confidence: 99%
“…2A and B). Thin sections of these cells were prepared and examined using the procedure described by Khmelenina et al (18). Major differences were observed between cells grown in nitrogen-sufficient and nitrogen-free media ( Fig.…”
mentioning
confidence: 99%